Kenaf Productivity as Affected by Agricultural Practices in Iowa. Issue 6 (28th September 2017) - Bourguignon, Marie; Moore, Kenneth; Lenssen, Andrew; Archontoulis, Sotirios; Stokke, Douglas; Baldwin, Brian
Abstract : Development and commercialization of biobased and bioenergy products contribute to new and expanded markets for agricultural feedstocks, reduce U.S. dependence on petroleum, and diversify agriculture. In Iowa, there are opportunities for development of manufacturing products from biobased feedstocks and the production of kenaf ( Hibiscus cannabinus L.), an annual, fast‐growing herbaceous crop. Different agronomic management practices from a single large field experiment were investigated for kenaf stem production in Iowa with the objectives to: (i) develop optimum agronomic practices (planting date, seeding rate, row spacing, N fertilization presence or absence) leading to optimal kenaf stem and fiber yield; (ii) assess the effects of crop management practices on kenaf morphology; and (iii) determine lignocellulosic composition of kenaf bast and core. Cultivar Tainung 2 was grown at Boone, IA, and measured at harvest for stem dry yield, stand density, stem height and diameter, core:bast ratio, and lignocellulose concentration. Results indicated that planting kenaf in early May in 20‐cm rows led to the greatest stem dry yields (13 Mg ha −1 ) and that 18.5 seed m −2 in 20‐cm was the optimal combination of practices for stem dry yield. Adding N was only favorable when kenaf was planted in early May. Crop management practices influenced stem height, diameter, and core:bast ratios; however, their effects on lignocellulose concentration in bast and core were nominal. It was concluded that kenaf responded well to Iowa's climate and that bast production could be improved by the selected agricultural practices.